2017
DOI: 10.1111/ecc.12794
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal communication approach in advanced lung cancer: A qualitative study of patients’, relatives’ and staff's perspectives

Abstract: Communication and the care of patients with advanced cancer are a dynamic, interactive and challenging process, often characterised in every day practice by discontinuity and lack of coordination. The objective of this study was to explore the patients' and family-caregivers' needs and preferences regarding communication, quality of life and care over the trajectory of disease. The second aim was to assess health professionals' views on a longitudinally structured, forward-thinking communication approach based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 40 publications
0
25
0
1
Order By: Relevance
“…The need for specific provision of psychological support [911,2–25] rather than a vague offer, shows clearly the necessity to revise the previously practised access to psycho-oncological measures. Villalobos et al [33] suggest the implantation of a longitudinal communication approach, to promote flexibility for respecting the individuality of patients with lung cancer, as one way of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The need for specific provision of psychological support [911,2–25] rather than a vague offer, shows clearly the necessity to revise the previously practised access to psycho-oncological measures. Villalobos et al [33] suggest the implantation of a longitudinal communication approach, to promote flexibility for respecting the individuality of patients with lung cancer, as one way of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…For MC 3, tumour progression and the facilitation of prognostic awareness are paramount. MC 4 focuses on the transition to best supportive care as all possible disease-modifying interventions are exhausted including patients preferences [11]. Additional file 3 (supplementary material) includes a detailed description of aspects and examples.…”
Section: Checklist For Mcsmentioning
confidence: 99%
“…In spite of knowing about the positive effects of communication, patients, caregivers and healthcare providers often perceive communication skills of healthcare staff to be suboptimal and fragmented. Therefore, training of communication skills is recommended [7,11] as well as a team approach to communication with patients, involving physicians and nurses. However, the actual application of communication skills in a team approach in routine practice remains difficult.…”
Section: Introductionmentioning
confidence: 99%
“…1 This suggests that quality of health professional-patient communication is linked to the quality of communication and coordination within the team, 2 and that informal caregivers also play a crucial role in managing patients' cancer disease. 3,4 Nevertheless, literature highlights that many clinical contexts are still lacking a good-quality patient-health professional communication regarding end-of-life preferences and prognosis disclosure, 5,6 and information preferences for patients with advanced cancer are still unmet. 7 As information transmission enables patients to make informed choices about their own healthcare, it can be said that, in cancer care, disclosure issue is still an ethically challenging clinical problem.…”
Section: Introductionmentioning
confidence: 99%
“…10 On the contrary, prognostic disclosure has been associated with more realistic patients' expectations of life expectancy, 11 and discussions on prognosis seem to strengthen the relationship between patient and oncologist. 12 Literature has also shown that good collaboration among health professionals is essential for high-quality care 4 and that patient-centred care is enhanced by both good inter-professional communication and acknowledgement of the interdependence of each one's role. 13 However, the perspectives of patients, caregivers, physicians and nurses have been seldom studied all together.…”
Section: Introductionmentioning
confidence: 99%